OPTIMALISASI PENGELOLAAN KAWASAN BELITONG UNESCO GLOBAL GEOPARK DALAM ASPEK KEBERLANJUTAN KELESTARIAN LINGKUNGAN - M. Rheivazha Azzah Karsyah; Neny Marlina (Journal of Politic and Government Studies, 2026)
The Belitong UNESCO Global Geopark (UGGp) is a geopark recognized by UNESCO for its unique geological, biological, and cultural values. However, during the 2024 UNESCO revalidation process, the Belitong UGGp received a yellow card, indicating several issues in the management of the area, particularly regarding the trade in satam stone, which lacks robust regulations, and the release of turtle hatchlings, which is not yet conducted professionally. These conditions highlight challenges in achieving geopark management aligned with the principles of environmental sustainability. This study aims to analyze the management of the Belitong UGGp area from the perspective of environmental sustainability using Jonathan B. Tourtellot’s geotourism theory, which emphasizes environmental conservation, community participation, and education. This study employs a qualitative research method with a descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving various stakeholders, such as the geopark management body, local government, local communities, and tourism operators. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The research focuses on the implementation of geotourism principles in area management, particularly regarding efforts to conserve geodiversity and biodiversity, community involvement in area management, as well as the implementation of environmental education programs for the community and tourists. Research findings indicate that the management of the Belitong UGGp has been guided by the principle of sustainability through various conservation programs, community engagement, and the organization of educational activities. Conservation efforts are carried out through the protection of geosites, mangrove ecosystem rehabilitation, turtle hatchling conservation, and the control of activities that have the potential to damage the environment. Community participation is evident through the involvement of tourism awareness groups, geopark communities, the development of geoproducts, and pentahelix collaboration. Meanwhile, the educational aspect is realized through the provision of interpretive panels, geotrails, digital media, and environmental outreach activities. However, the study found that several challenges remain, such as the lack of optimal regulations for the protection of satam stones, uneven management capacity across geosites, limited evaluation of educational impacts, and the need for strengthened oversight of tourism activities that pose risks to the environment.